(untitled) (Journal of Hama University, 2025)
Several guidelines have been published advocating the use of regenerative endodontic therapy (RET) in managing vital and non-vital immature and mature permanent teeth. It is unclear; however, how many Syrian dentists and endodontists routinely use this technique and their opinion of its outcomes, and barriers to its use. This research aims to explore the opinions and behavior of general practitioners and Endodontists in Syria regarding Regenerative endodontic therapy in permanent teeth, and the materials used in this Procedure. The sample consisted of 415 endodontists and general practitioner dentists in Syria. The questionnaire consisted of 7 questions about Regenerative endodontic therapy in permanent teeth. The results showed that 73.6% of the participants had prior knowledge about the Regenerative endodontic therapy procedure. 31% of the participants had performed a Regenerative therapy, revascularization was the most widely used method by the participants with a percentage of 89%, and the main reason that prompted practitioners to perform Regenerative therapy was irreversible pulpitis. Most of the participants promised this procedure a phased procedure by 73%, and the greatest fear was apical lesion formation after the procedure 88% The data was analyzed after being collected from the participants using chi-square analysis at a significance level of 0.05.